Intraoperative Anaphylaxis Reaction Due to Suspected Anesthesia Agent - Sukmono, Raden Besthadi; Febri, Rafli Nur (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Background: Intraoperative anaphylaxis is a life-threatening condition that may present atypically without cutaneous or respiratory manifestations, making early diagnosis challenging. Case Presentation: A 24-year-old male (ASA II) with sinus bradycardia and three previous uneventful general anesthetics underwent left auricular mass extirpation under general anesthesia. Approximately 90 minutes after induction, the patient developed sudden tachycardia despite minimal surgical stimulation. No additional epinephrine infiltration had been administered. Body temperature was normal and sevoflurane MAC was 0.7. Initial management included a 200 mL crystalloid fluid challenge, fentanyl 2 µg/kg IV bolus, and reduction of sevoflurane MAC to 0.5; however, tachycardia persisted and severe hypotension ensued (from 100/60 mmHg to 50/30 mmHg). No rash, bronchospasm, or fever was observed. Suspected intraoperative anaphylaxis was treated with epinephrine 0.1 mg IV (two doses), 500 mL crystalloid bolus, and supine positioning. Tachycardia resolved after the first epinephrine dose, and blood pressure improved after the second dose. Conclusion: This case highlights that intraoperative anaphylaxis can occur without skin or airway manifestations, consistent with World Allergy Organization (WAO) criteria. Prompt recognition and early epinephrine administration are crucial to improving patient outcomes